Using large ensemble modelling to derive future changes in mountain specific climate indicators in a 2 and 3°C warmer world in High Mountain Asia. (18th August 2020) - Bonekamp, P. N. J.; Wanders, N.; van der Wiel, K.; Lutz, A. F.; Immerzeel, W. W.
Abstract: Natural disasters in High Mountain Asia (HMA) are largely induced by precipitation and temperatures extremes. Precipitation extremes will change due to global warming, but these low frequency events are difficult to analyse using (short) observed time series. In this study, we analysed large 2000 year ensembles of present day climate and of a 2 and 3°C warmer world produced with the EC‐Earth model. We performed a regional assessment of climate indicators related to temperature and precipitation (positive degree days, accumulated precipitation, [pre‐ and post‐] monsoon precipitation), their sensitivity to temperature change and the change in return periods of extreme temperature and precipitation in a 2 and 3°C warmer climate. In general, the 2°C warmer world shows a homogeneous response of changes in climate indicators and return periods, while distinct differences between regions are present in a 3°C warmer world and changes no longer follow a general trend. This non‐linear effect can indicate the presence of a tipping point in the climate system. The most affected regions are located in monsoon‐dominated regions, where precipitation amounts, positive degree days, extreme temperature, extreme precipitation and compound events are projected to increase the most. Largest changes in climate indicators are found in East Himalaya, followed by the Hindu Kush and West and Central Himalaya regions. Western regions will experience drier summers and wetter winters, while monsoon dominated regions drier winters and wetter summers and northern regions a wetter climate year round. We also found that precipitation increases in HMA in a 3°C warmer world are substantially larger (13%) compared to the global average (5.9%). Additionally, the increase in weather extremes will exacerbate natural hazards with large possible impacts for mountain communities. The results of this study could provide important guidance for formulating climate change adaptation strategies in HMA. Abstract : Natural disasters in High Mountain Asia are largely induced by precipitation and temperatures extremes. In this study we analysed large 2000 year ensembles of present day climate and of a 2 °C and 3 °C warmer world and show mountain specific climate indicators have different regional responses to temperature rise. Largest changes are found in the Eastern Himalaya region. This study could provide importance guidance for climate change adaptation strategies in HMA. Regional summary of change in climate indicators compared to present day (PD), normalized by the 3 degrees warmer world for 6 out of 15 studied regions. Each climate indicator is normalized by the maximum regional value: a value of 1 for a specific region and climate indicator means this climate indicator changed the most in that region compared to the other regions, EP, extreme precipitation (P95); ET, extreme temperature (T95); MD, melt days; PA, yearly solid precipitation sum; PpreM, precipitation during pre‐monsoon; PM, monsoon precipitation; PposM, precipitation during post‐monsoon; PDD, positive degree days; PT, compound event when both precipitation and temperature exceed the PD 95% percentile. The climate indicator change between 2°C and PD is indicated in blue, the change between 3°C and PD in red. Data are aggregated using all cells in a region, except for PDD and PA, where only glacier and/or snow‐covered (at least 1 month a year) cells are considered.